THE EFFECT OF ASSESSMENT FOR LEARNING IN IMPROVING NON-NATIVE ADULTS PERFORMANCE IN MALAY LANGUAGE - Muniandy, Punitha Vathi; Othman, Abdul Jalil B; Jamaluddin, Sharir B (PEOPLE: International Journal of Social Sciences, 2019)
Assessment for learning is one of the teaching and learning process that has been adopted to improve and accelerate learners’ ability in their learning especially involving modern foreign language. However, the process of learning becomes more productive when Assessment for learning is implemented in an informal approach for non-native adults. Therefore, the study focused on the implementation of an informal assessment for learning in a Malay language course that is being taught as modern foreign language among non-native adult learners in a higher learning institution. Malay as a modern foreign language is still new at piloting stage in Malaysia. As a result, it would be useful to adopt assessment for learning informally for non-native adults acquiring the proficiency in an intense period. So, qualitative approach, an action research methodology has been undertaken as it also equally features of Assessment for learning and in parallel to accelerating adult learners’ proficiency especially at beginners’ level. Moreover, action research methodology is used to study the effectiveness of Assessment for learning applied among non-native adult learners in the Malay course. The research study involved 30 non-native adult learners in a higher learning institution from January 2014 until December 2017. The instruments used to collect data were by means of feedback, observation and continuous assessments. The data were analyzed in a quantified approach using descriptive research method to measure the frequency of non-native adult learners’ achievement by using Likert scale rating. The main findings of this research revealed how informal Assessment for learning assists non-native adult learners achievements and also benefits trainers in future to adopt and apply such model to support their teaching and elevate non-native adult learners’ achievement in Malay course.